2004
DOI: 10.1207/s15327078in0501_1
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Course of Habituation in Infancy and Preschool Outcome

Abstract: A longitudinal sample of 226 infants were tested monthly on habituation and novelty preference tasks, augmented with simultaneous heart rate recording from 3 to 9 months of age. Infants were then administered the Bayley Scales of Infant Development II (BSID) and MacArthur Communicative Development Inventory (MCDI) at 12, 18, and 24 months. Prior findings regarding the decline in look duration with age were replicated. Age‐based factors were extracted from the monthly assessments, an early attention factor from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
154
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(175 citation statements)
references
References 63 publications
19
154
2
Order By: Relevance
“…The speed at which information can be encoded is thought to be one of the main components of intelligence in adults (Vernon, 1987) as well as in infants (Colombo, Shaddy, Richman, Maikranz, & Blaga, 2004;Rose, Feldman, & Jankowski, 2002). Speed of processing and recognition memory both can be assessed using a novelty preference paradigm that measures an infant's tendency to direct visual attention toward a novel stimulus rather than a familiar one (Rose, Feldman, & Jankowski, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The speed at which information can be encoded is thought to be one of the main components of intelligence in adults (Vernon, 1987) as well as in infants (Colombo, Shaddy, Richman, Maikranz, & Blaga, 2004;Rose, Feldman, & Jankowski, 2002). Speed of processing and recognition memory both can be assessed using a novelty preference paradigm that measures an infant's tendency to direct visual attention toward a novel stimulus rather than a familiar one (Rose, Feldman, & Jankowski, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…First, studies of information processing in the first year of life have found preterms to be slower at encoding information than full-terms, and to have poorer recognition memory, recall memory, and attention (de Haan, Bauer, Georgieff, & Nelson, 2000;Miranda & Fantz, 1974;Rose, 1980Rose, , , 1983Rose, Feldman, & Jankowski, 2001Sigman & Parmelee, 1974;Spungen, Kurtzberg, & Vaughan, 1985). Second, the newer infant information processing abilities have been found to predict IQ and language in later childhood and early adolescence (Colombo, Shaddy, Richman, Maikranz, & Blaga, 2004;Dougherty & Haith, 1997;Fagan, 1984;Fagan & Haiken-Vasen, 1997;Fagan & McGrath, 1981;McCall & Carriger, 1993;Rose & Feldman, 1995;Rose, Feldman, & Jankowski, 2003a;Sigman, Cohen, Beckwith, Asarnow, & Parmelee, 1991;Thompson, Fagan, & Fulker, 1991). …”
mentioning
confidence: 99%
“…By knowing the relation between childhood stuttering and attention regulation in different levels of emotional arousal, future work can be done to prevent the severity of stuttering. Numerous studies have been conducted with infants and their looking durations to measure cognitive processing abilities and these early processing abilities can predict later cognitive development (Jankowski, Rose, and Feldman 2001;Frick, Colombo, and Saxon 1999;Colombo, Shaddy, Richman, Maikranz, and Blaga 2004;Richards and Cronise 2000). Although some early indicators of childhood stuttering are known today, present findings suggest that acquiring more objective knowledge of the cognitive processing characteristics of children who stutter should enhance our ability to identify, assess, prevent, and treat early childhood stuttering.…”
Section: Resultsmentioning
confidence: 77%